2010
DOI: 10.1590/s0103-51502010000100006
|View full text |Cite
|
Sign up to set email alerts
|

Distúrbios osteomusculares e o trabalho dos que cuidam de idosos institucionalizados

Abstract: ResumoIntrodução: Os distúrbios osteomusculares relacionados ao trabalho continuam comuns entre trabalhadores, e permanece a preocupação dentro do tema "Promoção à saúde no trabalho". Objetivo: Investigar, em instituições na cidade de Curitiba, PR, as relações existentes entre as desordens osteomusculares de trabalhadores que cuidam de idosos, as condições de trabalho e a capacidade funcional dos idosos. Materiais e métodos: Consistiram de elaboração de questionário contendo: dados demográficos, questões relac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
8

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
1
4
0
8
Order By: Relevance
“…Similar studies show a high occurrence of musculoskeletal disorders in nursing professionals over the previous 12 months, where the predominance of pain is localized in the upper limbs between 80% to 93%. 6,10,18,19 This data confirms the study by Alencar et al 4 who found symptoms of musculoskeletal pains over the previous 30 days in 62.7% of the workers, with the most prevalent pains in the lumbar and cervical regions, in the shoulders, and in the knees. The pace of work, time pressure, and insufficiency of employees for the demand also influenced the presence of musculoskeletal pain, which leads to the conclusion that factors related to the organization of work had influenced musculoskeletal disorders.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar studies show a high occurrence of musculoskeletal disorders in nursing professionals over the previous 12 months, where the predominance of pain is localized in the upper limbs between 80% to 93%. 6,10,18,19 This data confirms the study by Alencar et al 4 who found symptoms of musculoskeletal pains over the previous 30 days in 62.7% of the workers, with the most prevalent pains in the lumbar and cervical regions, in the shoulders, and in the knees. The pace of work, time pressure, and insufficiency of employees for the demand also influenced the presence of musculoskeletal pain, which leads to the conclusion that factors related to the organization of work had influenced musculoskeletal disorders.…”
Section: Discussionsupporting
confidence: 89%
“…3,4 Among health professions, nursing, in particular, has been affected by musculoskeletal disorders. Studies made in many countries show a prevalence higher than 80% occurring among nursing professionals, and Brazilian studies show prevalence of 93% of these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Quanto à prevenção da lombalgia é preciso uma avaliação da coluna lombar analisando o relacionamento da dor quanto a atividades que exigem algum tipo de esforço físico, postural, movimento, tensão emocional 40 .…”
Section: Prevençãounclassified
“…Nas instituições asilares há um grande nú-mero de idosos residentes e dependentes da assistência de profissionais da saúde, em especial, dos profissionais da enfermagem que compõem o maior quadro de funcionários nessas instituições 7 . Devido ao grande número de idosos institucionalizados e às condições muitas vezes precárias dessas instituições, há riscos à saúde dos trabalhadores 8 . O trabalho de técnicos e auxiliares de enfermagem, em geral, é desgastante, pois o ambiente de trabalho é instável e agitado e as atividades são intensas, interferindo na vida social e emocional dos trabalhadores 5 .…”
Section: Introductionunclassified